Die Siedlungsstruktur auf Als in der älteren Eisenzeit - Ketelsen, Solveig (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
Looking on a map, the island of Als has a very interesting location – close to the mainland, while still being surrounded by the sea. Due to its location close to the mainland of Sønderjylland, its political affiliation changed repeatedly in historical times, which is also being discussed for prehistoric times. Bearing this in mind, the development of the settlement structure on Als during the Early Iron Age (c. 500 BC – AD 350) was investigated as part of a Master’s thesis, especially regarding characteristic types of longhouses. The results are presented here. For the first time an attempt has been made to collect and analyse all the material available from Museum Sønderjylland – Arkæologi’s finding reports. It is demonstrated that the overall picture of the settlement structure on Als and its development during the Early Iron Age is quite consistent, even though there are few regional and chronological differing tendencies. Furthermore each period from the Early Pre-Roman Iron Age to the Late Roman Iron Age seems to be dominated by one specific longhouse type. The connection to mainland building traditions cannot be overlooked, but still the settlements on Als developed their own regional traits.